Colloidal Assembly Approaches to Micro/Nanostructures of Complex Morphologies - Xu, Wenjing; Li, Zhiwei; Yin, Yadong (Small (Weinheim an der Bergstrasse, Germany), 2018)
The ability to programmatically assemble colloidal micro/nanostructures into highly ordered superstructures is of great importance in both fundamental studies and practical applications. In addition to the sophisticated manipulation of the short‐range and long‐range interactions imposed on the colloidal building blocks, the intrinsic shape elements including face, edge, corner, concave, convex, and curvature also play very important roles in solving the “jigsaw puzzle” of the superstructures. Here, the recent progress in the development of colloidal assembly strategies for the formation of complex superstructures is reviewed, with a primary focus on the unique effects of the morphology of the building blocks to the assembly processes and the final structures. Overall, this Review aims to shed light on the fundamental understanding of the colloidal behaviors of complex micro/nanostructures and promote the continued development of effective strategies for the creation of functional materials with complex compositions and morphologies. Colloidal assembly of micro/nanostructures represents one of the most effective approaches to achieve highly ordered superstructures. Here the recent progress of colloidal assembly strategies is reviewed, especially the unique effects of morphology of the building blocks to the assembly process.